La memoria escrita de la Casa de Granada: El Archivo del Marquesado de Campotéjar (s. XV-1643) / The Written Memory of the House of Granada: the Archive of the Marquesado de Campotéjar (15th century-1643). - García Luján, José Antonio (Historia. Instituciones. Documentos, 2017)
RESUMEN: A partir del inventario judicial de bienes realizado en 1643 al morir don Pedro de Granada Venegas Manrique de Mendoza, primer marqués de Campotéjar, se analiza la historia del archivo de la Casa de Granada, su organización y los documentos que contenía, en su mayoría conservados durante siglos en la Casa de los Tiros de Granada y trasladados a principios del siglo XX a Italia, donde hoy se hallan. ABSTRACT: In 1643, following the death of “Don Pedro de Granada Venegas Manrique de Mendoza”, the first “ Marqués de Campotéjar”, a legal property inventory was carried out . The history of the archive of the House of Granada was analyzed, as well as its organization and documents contained within, kept for centuries in “Casa de los Tiros” in Granada and most of which was transferred at the beginning of the twentieth century to Italy, where they are still today.